Women Leaders Transcending the Demands of Covid-19: A Positive Psychology 2.0 Perspective - Mayer, Claude-Hélène; May, Michelle S. (Frontiers in Psychology, 2021)
This article explores selected speeches of three global women leaders during the time of the Covid-19 pandemic from positive psychology perspectives. It focuses on speeches to address and manage the pandemic of global women leaders, such as Angela Merkel (Germany), Jacinda Ardern (New Zealand), and Tsai Ing-Wen (Taiwan). This study explores the question what global women leaders' leadership actions and responses are and how they address their nations with regard to the four pillars of PP2.0 and the PURE model during Covid-19. The study uses a post-modernist qualitative research design. It is anchored in the hermeneutical-phenomenological research paradigm, using leadership theories and PP2.0 as a lens to explore and understand their strengths with regard to the Covid-19 pandemic. The authors use thematic analysis to analyse the selected speeches made by the three women leaders at the onset of the pandemic in Germany, New Zealand and Taiwan. The study contributes to improve the understanding of global women leadership during Covid-19. Conclusions are drawn. Recommendations will be made accordingly.